STUDI LITERATUR MODAL KERJA PADA BEBERAPA JURNAL PERIODE 2012-2022 - Engel, Paska Elia; Pasaribu, Regita Paskah; Melanie, Vivian -; Meiden, Carmel - (Universitas Madura, 2023)
The purpose of working capital management is to review and monitor the optimal balance between each component of working capital so that it can be used in the process of increasing profitability. Working Capital is a term in the field of business which means net working capital. The meaning of net working capital is that there is a difference between the company's total assets and liabilities in a certain period of time. This study aims to determine the development of the influence on working capital management and financial ratios on profitability in several journals. Although many studies have been carried out between working capital and profitability, most of the research results still have a phenomenon, namely the recognition of working capital as one of the important variables to regulate company profitability. The influencing factors are proxied by focusing on profitability centered on Return On Assets. The sample of this research is 30 journal articles. Data collection uses several journals published between 2012-2022 using a purposive sampling technique. The results show that the countries that have researched the Working Capital theme the most are Indonesia and Kenya.